The Development of Learning Chinese Vocabulary Achievement by Integrating to the Theory of Multiple Intelligences for Grade 1 at Srikird Municipality School 1 - Yortkate, Hataitip; Phunsapphaisan, Thanon (Journal of Sinology (วารสารจีนวิทยา), 2017)
This research study is the results of integrating to the theory of multiple intelligences for grade 1 students at Srikird Municipality School 1. The samples of this study are the 32 students in grade 1/3 . The research instruments are the learning plan integrated theory of Multiple Intelligences , the learning achievement test and the behavior observing theory of Multiple Intelligences . The data was analyzed by using descriptive statistics and t-test . Research findings were as followed ; 1 ) 89.06 , 91.25 and 80.00 percentages resulted in the achievement of learning Chinese vocabulary by integrating to the theory of multiple intelligences of grade 1 students . 2 ) The student’s achievement was increased after integrating to the theory multiple intelligences in significant 0.05 levels.